The Emotion Profile of Web Search - Kazai, Gabriella; Thomas, Paul; Craswell, Nick (Proceedings of the International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR), 2019)
Emotions are an essential part of most human activities, including decision-making. Emotions arise in response to information, e.g., presented in web pages, and are also expressed in the words used to convey that information in the first place. In this paper, we study the emotion profile of retrieved and clicked web search results towards the goal of better understanding the role of emotions in web search. Using click logs from a four-month period, up to the end of January 2019, we examine the emotions associated with search results and contrast them to the emotions of clicked results, taking rank and relevance into account. Emotions are assigned to web pages based on two lexicons: SentiWordNet (positive, negative and objective sentiments) and EmoLexData (afraid, amused, angry, annoyed, don't care, happy, inspired, and sad emotions). We look at the sentiment/emotion profiles of search results grouped around a set of controversial and mundane topics and hypothesise that users are more likely to click emotionally charged results than emotionless results, both in general, and in particular when their query relates to controversial topics.